The impact of 9P’s of marketing mix strategy towards the decision to purchase halal tourism services - Lorena Dara Putri Karsono; Laila Fairuz Salma (Department of Islamic Economics, Islamic University of Indonesia, 2023)
IntroductionHalal tourism has become one of the trends in the tourism industry, including in Indonesia. However, the research on character education-based halal tourism is still limited in number. ObjectivesThis study aims to analyze the impact of the 9P's of the Marketing Mix strategy on purchasing decisions at PT Gaido Travel & Tours, Kudus Branch, a provider of character education-based halal tourism services. MethodThis quantitative study uses convenience sampling to collect data from of 100 prospective customers who expressed interest in PT Gaido Travel & Tours, Kudus Branch, services. The questionnaire utilized a five-point Likert scale, ranging from 1 to 5, to capture participants' perceptions and opinions related to the research variables. ResultsThe result shows that all the variables ie. product, price, promotion, place, physical evidence, people, processes, productivity, and priority, positively influence purchasing decisions both individually and simultanously. Furthermore, the model in this study can explain approximately 60.6% of the variation in purchasing decision of character education-based halal tourism services. ImplicationsThe company to uphold exemplary customer service and continuously enhance the execution of the 9P's of Marketing Mix strategy. This entails fostering a culture where employees are attentive to customer needs and refining the price strategy by incorporating enticing features that aligns with industry standards.Originality/NoveltyThis study provides insights on how 9Ps of the Marketing Mix strategy can be implemented for a character education-based halal tourism services provider.